Not just one language, not just one literature. Readings, writings and «translations» from Latin America - Vázquez, María Celia (Universidad Nacional del Litoral, 2019)
The experiences of bilingual or multilingual Argentine and Latin American writers are the privileged object of this dossier, and one of its objectives consist is to think that situation in terms of instability: towards the subject, towards the so-called mother tongue, towards literatures, towards temporality, towards the territorial link. The problem of translation (from the biographical perspective or the auto-figuration of the translator to the perspective of the translator) accompanies and modulates a thought that does not have the figure of a path; it is, instead, the figure of an incessant relationship.